Development of a hoverboard / Siti Rafhanah Suwandi - Suwandi, Siti Rafhanah (2023)
Hoverboarding is a mode of personal transportation that allows people to get to their destination quickly without becoming physically tired as they would if they were walking. Walking can be tiresome, especially when the distance travelled is long. Furthermore, because they are fully reliant on humans, the time and energy required are both high. The main objective is to construct and test a hoverboard for students to use on their daily walks to and from class. The motors on the hoverboard in this build are controlled by pedals and are powered by DC batteries. When the pedals are pressed or loaded, the engine beneath the platform turns the tires connected to it. It's also made such that when people ride it, the board would naturally balance thanks to the use of balancing concepts in mechanical methods, prevent any mishaps. When compared to walking, it is expected to save students time and energy